The extraction of dissolved matter from porous materials - Chanh, Trương Minh (Vietnam Journal of Mechanics, 1981)
The extraction of dissolved matter from monodispersive of porous spheres and polydispersive mixture of spheres having different radii are considered within the framework of the generalized - diffusive theory. The obtained solutions are generalized as the classical results and can be used to define the kinematic coefficients.